Predictors of Attendance in Health and Wellness Treatment Groups for People with Serious Mental Illness - Phalen, Peter L. (Psychiatr Rehabil J, 2019)
OBJECTIVE: People with serious mental illness have dramatically reduced life expectancy that is largely attributed to elevated rates of chronic medical conditions. Several group interventions have been developed and implemented in recent years in order to improve health and wellness among people with mental health conditions. Unfortunately, attendance in these interventions is often low, and there is limited understanding of factors that influence patient engagement in this treatment modality. METHOD: Participants (N=242) were enrolled in one of two group-based health and wellness treatment programs. Using descriptive statistics and regression, we assessed treatment attendance and a range of potential predictors of attendance. RESULTS: We found lower attendance among people who were younger, people with more medical conditions, and people with more emergency room visits in the six months prior to the beginning of treatment. Younger age was a particularly strong predictor of low attendance and was the only variable significantly associated with attending zero treatment sessions. CONCLUSIONS AND IMPLICATIONS FOR PRACTICE: These results highlight the need for strategies to improve engagement of patients with poorer objective indicators of medical health, and patients with younger age.